1991
DOI: 10.1029/90eo00354
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Cerro Hudson SO2 clouds

Abstract: The Cerro Hudson volcano in southern Chile (45.92°S, 73.0°W) emitted large ash and sulfur dioxide clouds on August 12–15, following several days of minor activity [Global Volcanism Network Bulletin, 1991]. The SO2 clouds were observed using (preliminary) near real‐time data from the Total Ozone Mapping Spectrometer (TOMS) as they encircled the south polar region. The injection of SO2 into the stratosphere has essentially created a gigantic chemical tracer that could provide new insights into the wind patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 1 publication
(1 reference statement)
0
26
0
Order By: Relevance
“…Published ice core flux estimates following the eruptions of Pinatubo and Tambora (Table ) are compared to the modeled deposition flux for the 17 and 45 Tg SO 2 injection experiments at the locations of the ice cores in the left‐hand panels of Figure . It should be noted that the Pinatubo sulfate signal in Antarctic ice cores includes a component from the eruption of Cerro Hudson, which injected about 1.5 Tg of SO 2 into the atmosphere—about 10% of that of Pinatubo [ Doiron et al ., ]. Error bars on the model values represent the 2‐sigma ensemble model variability.…”
Section: Resultsmentioning
confidence: 96%
“…Published ice core flux estimates following the eruptions of Pinatubo and Tambora (Table ) are compared to the modeled deposition flux for the 17 and 45 Tg SO 2 injection experiments at the locations of the ice cores in the left‐hand panels of Figure . It should be noted that the Pinatubo sulfate signal in Antarctic ice cores includes a component from the eruption of Cerro Hudson, which injected about 1.5 Tg of SO 2 into the atmosphere—about 10% of that of Pinatubo [ Doiron et al ., ]. Error bars on the model values represent the 2‐sigma ensemble model variability.…”
Section: Resultsmentioning
confidence: 96%
“…The near‐zero Δ 33 S (−0.09‰) of Cerro Hudson sulfate indicates that the sulfate was formed primarily through a mass dependent process. Observations during the atmospheric distribution and transport of the 1991 Cerro Hudson SO 2 clouds indicated that the eruption was a predominantly upper tropospheric/lower stratospheric (11–16 km) event [ Cacciani et al , 1993; Schoeberl et al , 1993]; the amount of sulfur emitted (1.5 Tg SO 2 ) was relatively small [ Doiron et al , 1991], with a substantial fraction of volcanic debris reaching Antarctica via the middle/upper troposphere (8–12 km) [ Deshler et al , 1992; Legrand and Wagenbach , 1999]. Volcanic SO 2 in the upper troposphere and lower polar stratosphere is not subjected to photodissociation since little high energy UV light (<220 nm) is available at this altitude, making it similar to the case of tropospheric aerosol and background sulfates.…”
Section: Resultsmentioning
confidence: 99%
“…Plentiful SO 2 , above 1500 Kt, produced by the Chile Hudson volcanic eruption (45°55′ S, 73°00′ W) in August 1991 is ejected into the atmosphere, and approaches 8% of 20 Mt released by Philippine Pinatubo volcano(15°08′ N,120°21′ E) in June 1991 [24] . The volcanic aerosol mass from Hudson eruption extended southward immediately due to the short distance between this volcano and Antarctica [25] , along with the relatively low altitude of particulate cloud mass.…”
Section: The Period Of 1800-1996 Admentioning
confidence: 99%